Comparing Childhood Characteristics of Adopted and Non-adopted Individuals Deceased by Suicide - Ligier, Fabienne; Body Lawson, Festus; Lamourette, Marilou; Giguère, Charles-Edouard; Lesage, Alain; Séguin, Monique (Frontiers in Psychiatry, 2022)
Objective: Across the globe more than 35,000 children a year are adopted by non-relatives, and some studies suggest that adopted individuals may be more vulnerable to developing mental disorders. To map the differences in suicide risk factors in adopted and non-adopted individuals, this study will compare the development of mental disorders as well as life events occurring before the age of 18 for both adopted and non-adopted individuals deceased by suicide. Methods: This study included 13 adopted and 26 non-adopted individuals deceased by suicide as well as 26 non-adopted living control individuals. Cases were taken from a data bank created over the last decade by researchers of [our institution] comprising a mixture of 700 suicide cases and living control individuals aged from 14 to 84. Adopted and non-adopted individuals deceased by suicide; adopted individuals deceased by suicide and non-adopted living control individuals were each compared on Axis I and II disorders, early life events, and burdens of adversity. Results: Results show significant differences, with a higher rate of Attention Deficit Hyperactivity Disorder, mental health comorbidity and Cluster C personality disorders among adopted individuals. Furthermore, adopted individuals have higher adversity scores prior to the age of 15. Conclusion: This study underlines the fact that adoptive families need to be supported throughout adoption. Health care professionals need specialized training on this matter, and the psychological challenges adopted individuals face need to be treated at the earliest juncture.